A qualitative inquiry into psychiatrists' perspectives on the relationship of psychological trauma to mental illness and treatment: implications for trauma-informed care. (2nd November 2021) - Isobel, Sophie; Gladstone, Brenda; Goodyear, Melinda; Furness, Trentham; Foster, Kim
Abstract: Background: Trauma is a factor impacting the lives of many people experiencing psychiatric disorders. Trauma affects people's responses to illness as well as their interactions with services. Aim: This study aimed to explore the understandings and experiences of psychiatrists of working with trauma and emerging models of Trauma-Informed Care. Methods: An interpretive qualitative inquiry was undertaken using semi-structured in-depth interviews with psychiatrists. Results: Four themes were identified: Making sense of trauma; A contentious relationship between trauma and mental illness; Treatment made more challenging by trauma; Trauma-Informed Care highlights tensions. Psychiatrists are familiar with the concept of trauma but there are differences in beliefs about its relationship to mental illness that are consequential for practice. Trauma-Informed Care is seen as an effort to humanise mental health services, but with perceived limited impact on psychiatrists' roles. Conclusion: Findings indicate need for further consultation and collaboration with psychiatrists around trauma-informed care implementation; as well as consideration of what is required to develop professional consensus on trauma and its relationship to illness.